IRIS PATTERN RECOGNITION AS AN INFALLIBLE MEAN OF IDENTITY ESTABLISHMENT IN FORENSIC CASEWORK - Sehrawat , JS (Journal of Forensic Medicine and Toxicology, 2021)
Biometrics is a mean of forensic recognition based onmeasurements and calculations of human body orbiological features. Human body features. Biometricidentification systems may make use of iris, retina,fingerprints, face, ear, gait parameters, facialphysiognomy, photogrammetric or geometry features, etc.for recognition and hence identification pursuits. The highsecurity areas like airports, nuclear reactors, thermal orhydro-electric power plants, legislative buildings, defenseestablishments etc., require secured entry of authorizedpersons. Biometric tools of recognition like automatic facerecognition system can play a crucial role in recognizingillegal intruders to such areas. Iris is an excellent trait tobe used in biometric system for recognition of anindividual due to its individualistic, unique, universaland inimitable features. In this article, the current nationaland international status of use of iris patterns for forensicrecognition, its advantages and limitations, and futureprospects have been presented.
Keywords: identification; Iris identification